Aid, structural change and the private sector in Africa - John Page (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2012)
This paper argues that official development assistance (foreign aid) is partly responsible for the lack of structural change in Africa. Africa's development partners have devoted too few resources and too little attention to two critical constraints to private investment, infrastructure and skills, focusing instead on easily understood, but potentially low impact regulatory reforms. A new aid strategy, one that catalyses private investment in high value added sectors, is needed. Support for strategic interventions to push non-traditional exports, support industrial agglomerations, build firm capabilities, and strengthen regional integration should anchor a new donor agenda to create good jobs and sustain growth.
Keywords: O14; O19; O25; O40; 330; aid; structural change; private sector; industry; exports; Entwicklungshilfe; Strukturwandel; Armut; Privatwirtschaft; Industrialisierung; Investitionsklima; Afrika